2018
DOI: 10.3233/cbm-171160
|View full text |Cite
|
Sign up to set email alerts
|

Screening and function analysis of hub genes and pathways in hepatocellular carcinoma via bioinformatics approaches

Abstract: In conclusion, the present study identified several hub genes, and cell cycle and metabolism-related pathways that may play critical roles in the tumorigenesis of liver cancer. Future validation laboratory experiments are required to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“… 51 High expression of CCNA2 is associated with reduced survival in patients with breast cancer and HCC. 52 , 53 CCNB1 and CCNB2 are the principal activators of CDK1 and, together with CDK1, they promote the G 2 /M transition. 54 , 55 Expression of CCNB1 changes periodically throughout the cell cycle, and is a crucial initiator of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“… 51 High expression of CCNA2 is associated with reduced survival in patients with breast cancer and HCC. 52 , 53 CCNB1 and CCNB2 are the principal activators of CDK1 and, together with CDK1, they promote the G 2 /M transition. 54 , 55 Expression of CCNB1 changes periodically throughout the cell cycle, and is a crucial initiator of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…The function of BUB1 as oncogene or tumor suppressor gene has been observed in various types of cancer, including breast cancer, pancreatic ductal adenocarcinoma, prostate and gastric cancer (12)(13)(14)(15). Several studies have demonstrated the unfavorable prognostic role of BUB1 in liver cancer based on bioinformatics analysis (16)(17)(18). However, the molecular biological function of BUB1 in liver cancer still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, downregulation of NDC80 was able to suppress the replication of HBV-associated HCC cells (42). Bound to MYC, AURKA, which has two functional non-synonymous polymorphisms (lle31Phe and Val57lle), was able to regulate tumor cell growth at the genetic level (43). It has been reported that AURKA lle31Phe enhances the proneness of HBV-infected individuals to develop liver cancer (44).…”
Section: Discussionmentioning
confidence: 98%